Two new genera of Trachyphloeini with a key to the genera of small terricolous South African Trachyphloeini and Embrithini (Coleoptera: Curculionidae: Entiminae) - Borovec, Roman; Skuhrovec, Jiří (Zootaxa, 2019)
Two new genera, Barclayanthus Borovec Skuhrovec, gen. nov. and Janakius Borovec Skuhrovec, gen. nov., assigned to the tribe Trachyphloeini Lacordaire, 1863, are described for three South African species of weevil: Barclayanthus micros Borovec Skuhrovec, sp. nov., B. cooteri Borovec Skuhrovec, sp. nov. and Janakius sylvaticus Borovec Skuhrovec, sp. nov. All species are illustrated and keyed. The taxonomic status of each of the new genera is discussed, and compared with similar genera of Trachyphloeini and Embrithini Marshall, 1942. A key to known small terricolous South African genera of both Trachyphloeini and Embrithini is included.
Keywords: brouci; Animals; Coleoptera; Weevils; zvířata; nosatcovití